Coping with Accession to the European Union
XI, 244 p.
Keywords: The book explores the role of new modes of governance in helping future member states to cope with their accession to the EU. It examines the extent to which civil society and business have assisted the governments of Southern, Central and Eastern European accession countries in taking on the ever more comprehensive body of EU laws and regulations.